The nexus of soil fertility, bioconcentration and soil pollution load in the tropical land use systems of Western Ghana - El Mellouki, Meryem; Boularbah, Ali; Kebede, Fassil (Frontiers in Soil Science, 2025)
Tropical agricultural soils are exposed to diverse management practices that influence soil fertility, trace metal accumulation, and food safety. Understanding how soil fertility interacts with trace metal uptake across crop systems is vital for sustainable tropical agriculture. This study assessed soil fertility, trace metal bioaccumulation, and pollution load across four land use systems, cacao (Theobroma cacao), oil palm (Elaeis guineensis), cocoyam (Xanthosoma sagittifolium), and maize (Zea mays) cultivated on Ferralsols and Acrisols in Western Ghana. Soil chemical properties, including total organic carbon (TOC), total nitrogen (TN), available phosphorus (P2O5), pH, exchangeable potassium (K), and cation exchange capacity (CEC), were analyzed to compute the Soil Fertility Index (SFI). Bioconcentration factors (BCFs) for Al, Cd, Cu, Mn, Ni, Zn, Sr, and Ti were determined from plant and soil concentrations, while contamination factors (CFs) and the Pollution Load Index (PLI) evaluated overall soil contamination. SFI values ranged from 0.41 ± 0.13 in Ferralsols under maize to 0.78 ± 0.26 in Acrisols under cacao. Cacao grown on Ferralsols exhibited the highest uptake of Mn (1.98 × 10⁻⁴ ± 1.15 × 10⁻⁴), Cu (1.70 × 10⁻³ ± 1.21 × 10⁻³), and Sr (2.32 × 10⁻³ ± 1.53 × 10⁻³), while maize and oil palm showed minimal accumulation, likely due to selective ion uptake and exclusion mechanisms. PLI values were uniformly low (1.56 × 10⁻⁵–8.08 × 10⁻⁵), indicating uncontaminated soils. SFI correlated strongly with BCF-Ni (r = 0.93), whereas Cd, Cu, and Zn uptake depended more on soil pH and organic carbon than overall fertility. PCA distinguished crop–soil elemental patterns, with Cu, Ni, Mn, Cd, and Ti dominant in cacao/Acrisol systems and Sr and Zn in oil palm/Ferralsol systems. Although soil was largely uncontaminated, elevated metal uptake in some systems (e.g., cacao/ Ferralsol) indicates that high fertility does not necessarily equate to soil health. Trace metal accumulation is primarily governed by plant specific ion selectivity and exclusion behaviors, warranting further investigation to define threshold ion concentrations for sustainable soil–plant health management).